Dengue virus harnesses mosquito Syntenin to load and secrete viral RNA into salivary exosomes - Florian Rachenne; Norman Schneider; Félix Rey-Cadilhac; Idalba Serrato-Pomar; Lauryne Pruvost; Laura Di Pietro; Jacques Dainat; Audrey Vernet; Chantal Cazevieille; Aurélie Ancelin; Joséphine Lai Kee Him; Sander Jansen; et al. (Proceedings of the National Academy of Sciences, 2026)
Viruses exploit extracellular vesicles (EVs) to transfer infection-enhancing viral RNAs. However, mechanisms underlying viral RNA loading remain elusive. We leveraged our previous discovery that dengue virus secretes transmission-enhancing subgenomic flaviviral RNA (sfRNA) into mosquito salivary EVs to investigate viral RNA loading mechanism. We demonstrate that sfRNA alone promotes the secretion of sfRNA-containing EVs marked by the mosquito EV biogenesis protein AeSyntenin, by applying microscopy and viral genetic editing in in vitro and in vivo models. SfRNA via its stem loop structures interacts intracellularly with mosquito AeSyntenin and this interaction is selectively maintained within EVs as shown by complementary RNA-affinity chromatography and RNA immunoprecipitation, and AI-based prediction. Finally, we used systemic and salivary gland-specific protein depletion to establish a functional role for mosquito AeSyntenin in exosome production and salivary secretion of sfRNA. We propose that sfRNA binds AeSyntenin to drive its selective packaging and release into exosomes, elucidating a mechanism for viral RNA incorporation into EVs.